Designing Task-Based English Speaking Materials for the Staff of Bank Mandiri Yogyakarta - Angelina, Patricia (LLT Journal: A Journal on Language and Language Teaching, 2017)
Most of the staff of Bank Mandiri in Yogyakarta have some difficulties to communicate with the foreign customers, which hinder the process of the service. Therefore, this study attempted to develop English speaking materials for the staff of Bank Mandiri in Yogyakarta using the principles of task-based learning. The writer adapted Kemps instructional design model (1977) comprising eight flexible, interdependent steps. Those steps, subsequently, were put under the umbrella of Borg Galls (1986) Research and Development (RD) method. Due to time and resource limitations, only three out of ten steps of the RD model were employed, which were: (1) Research and information collecting, (2) Planning and (3) Developing preliminary form of product. To acquire required information for developing the materials, the writer distributed needs analysis questionnaire to twenty staff of Bank Mandiri, Yogyakarta. The designed materials covered eight units. Each unit consisted of five sections, namely Do You Remember?, Prepare Yourself!, Can You Do These?, Lets Learn!, and Its Time to Write. It was expected that the materials could improve the speaking skill of the staff of Bank Mandiri Yogyakarta.